Analisis Konstruksi Kapal Ikan Berbahan Fiber Reinforced Plastic di Puger dengan Menggunakan Metode Elemen Hingga - Pratama Yuli Arianto; Awang Dika Pratama; Sumarji; Alfian Andhika Putra; Gaguk Jatisukamto (Politeknik Negeri Madura, 2025)
Most fishing vessels used by local fishermen in Puger are constructed from Fiberglass Reinforced Plastic (FRP). These vessels are still built using traditional methods, where the design is based on pre-existing models that are subsequently modified. As a result, the structural strength of the vessels when operating in the waters of Jember remains uncertain. Therefore, an analysis is required to determine the maximum load-bearing capacity of the vessel structure under marine operating conditions. This study involved field measurements and interviews with local fishermen to collect data on the vessels principal dimensions, geometry, cargo weight, and load positioning. The collected data were used to develop a structural model, which was then simulated using Ansys Workbench for Student 2024 Version R1 to analyze the loading conditions experienced by the vessel. The simulation results yielded Von Mises stress and deformation values for five different loading scenarios. The equivalent stress values obtained were 3.617 MPa, 2.8763 MPa, 2.8198 MPa, 3.4382 MPa, and 3.2877 MPa, respectively. Meanwhile, the corresponding deformation values were 0.41003 mm, 0.18602 mm, 0.17995 mm, 0.35096 mm, and 0.30843 mm. The analysis indicates that the highest equivalent stress occurred under the first loading condition, with a value of 3.617 MPa, which remains below the allowable stress limit of the material, defined as 9.46 MPa.